2007
DOI: 10.1111/j.1442-2042.2007.01911.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of risedronate on bone loss in men receiving androgen‐deprivation therapy for prostate cancer

Abstract: Aim: Androgen-deprivation therapy for prostate cancer decreases bone mineral density and increases the risk of fracture. The effect of risedronate, a potent third-generation oral bisphosphonate, on bone loss during androgen deprivation therapy was investigated. Methods: Sixty-one prostate cancer patients with a mean age (ϮSD) of 79 Ϯ 6 years who had received androgen deprivation therapy for 42 Ϯ 29 months were enrolled , and were treated with 2.5 mg of risedronate daily for six months. Bone mineral density was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 31 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…16 On the other hand, oral bisphosphonates including risedronate also have been developed for their convenient administration. Ishizaka et al 17 reported that risedronate prevented bone loss of the femoral neck and can reverse bone loss of the lumbar spine in men receiving ADT for PCa. This was the first report confirming the effect of risedronate on bone loss in PCa patients treated with ADT.…”
Section: Discussionmentioning
confidence: 99%
“…16 On the other hand, oral bisphosphonates including risedronate also have been developed for their convenient administration. Ishizaka et al 17 reported that risedronate prevented bone loss of the femoral neck and can reverse bone loss of the lumbar spine in men receiving ADT for PCa. This was the first report confirming the effect of risedronate on bone loss in PCa patients treated with ADT.…”
Section: Discussionmentioning
confidence: 99%
“…[13] showed that risedronate prevented bone loss of the femoral neck and can reverse bone loss of the lumbar spine in men receiving ADT for prostate cancer. Sixtyone men with a mean ( SD ) age of 79 (6) years who had been on ADT for 42 (29) months were treated with 2.5 mg oral risedronate daily for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…The effect on the reduction of osteoporotic fractures has been demonstrated for treatment with alendronate, risedronate, ibandronate, etidronate and zoledronic acid. The effectiveness in reducing vertebral and nonvertebral fractures were confirmed by many studies (73,74,75). The optimal regimen for zoledronic acid is unclear, because one study recommends treatment every 3 weeks (76), while another trial has produced similar results with an annual injection (77), and finally, another study reports that single infusion of zoledronic acid in patients receiving ADT reduces bone mineral loss and maintains BMD at least for 12 months during ADT (78).…”
Section: Ca Supplementationmentioning
confidence: 99%